2014
DOI: 10.1002/asia.201402766
|View full text |Cite
|
Sign up to set email alerts
|

Zinc–Porphyrin Dyes with Different meso‐Aryl Substituents for Dye‐Sensitized Solar Cells: Experimental and Theoretical Studies

Abstract: A series of new zinc-porphyrin dyes that contain different meso substituents (phenyl, carbazole phenyl, and carbazole thiophenyl groups) and bithiophenyl cyanoacrylic acid as the π-conjugated anchoring moiety were designed, synthesized, and characterized as sensitizers for dye-sensitized solar cells (DSSCs). The effects of these meso substituents on the properties of the porphyrin dyes were theoretically and experimentally investigated. By meso substitution of the porphyrin ring with carbazole-aryl moieties, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 95 publications
1
10
0
Order By: Relevance
“…The calculated results revealed that phosphazene containing dyes 2 , 4 , 6 , 8 , and 10 have larger μ normal and n c values than corresponding dyes 1 , 3 , 5 , 7 , and 9 (Table ). We have also extended our study with dye−(TiO 2 ) 38 cluster model which has been demonstrated reliable simulation of the dye–TiO 2 surface . In this case we have also observed that the dye 2 −(TiO 2 ) 38 system has larger μ normal value than the dye 1 −(TiO 2 ) 38 (Figure ).…”
Section: Resultssupporting
confidence: 61%
“…The calculated results revealed that phosphazene containing dyes 2 , 4 , 6 , 8 , and 10 have larger μ normal and n c values than corresponding dyes 1 , 3 , 5 , 7 , and 9 (Table ). We have also extended our study with dye−(TiO 2 ) 38 cluster model which has been demonstrated reliable simulation of the dye–TiO 2 surface . In this case we have also observed that the dye 2 −(TiO 2 ) 38 system has larger μ normal value than the dye 1 −(TiO 2 ) 38 (Figure ).…”
Section: Resultssupporting
confidence: 61%
“…The obtained efficiency was about 6.24%; the improved efficiency is due to the suppression in the aggregation of dye molecules and enhanced charge separation and charge injection [56]. The best result was obtained for dyes modified by carbazole phenyl group at the meso position.…”
Section: Recent Progress In Metal-free Sensitizers For Dsscsmentioning
confidence: 94%
“…The best result was obtained for dyes modified by carbazole phenyl group at the meso position. The obtained efficiency was about 6.24%; the improved efficiency is due to the suppression in the aggregation of dye molecules and enhanced charge separation and charge injection [56].…”
Section: Recent Progress In Metal-free Sensitizers For Dsscsmentioning
confidence: 94%
“…This is ascribed to the anchoring of the dye through its carboxylic acid groups to TiO 2 , a phenomenon that is commonly observed in the spectral responses organic sensitizers with carboxylic acid groups adsorbed onto TiO 2 films [33,34]. The broadness of the UV-vis absorption spectrum of ZnP-triazine-(gly) 2 adsorbed onto TiO 2 indicates its efficient light harvesting ability, making it suitable for use as sensitizer in DSSCs.…”
Section: Photophysical Propertiesmentioning
confidence: 96%